(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current research aims to analyze the content of the science book for the first intermediate grade in accordance with the international (TIMSS, 2019) standards, a list of (TIMSS) standards has been built that must be available in the content of the science book for the first intermediate grade to achieve this goal, and after reviewing a set of literature, studies and research, a list of TIMSS standards was reached in its initial form, which consisted of two dimensions: after the content, which includes four main requirements: (Biology - Chemistry - Physics - Earth Sciences) where it included the requirements of Biology (6) main criteria, the requirements of chemistry include (3) main criteria, physics requirements include (5) main standards, and Earth sciences include (4) main standards, the list was presented to a group of arbitrators and specialists in curricula and teaching methods, thus, the final list consisted of (18) criteria as a total sum of the criteria of the four main requirements, as for the cognitive dimension: which included three areas (knowledge - understanding - application), the field of knowledge included (3) standards and the field of understanding (8) standards and the field of application (5) standards, and a final total of (16) standards for the three areas.The researcher analyzed the content of the science book for the first intermediate grade in the light of the list that was built, and the idea was adopted as a unit for recording, and repetition as a unit for enumeration, they unanimously agreed on the validity of the analysis, and using the Holsti equation, the stability of the analysis was calculated in agreement with external analysts and with the researcher himself, thus the results of the content dimension analysis of the science book for the first grade average were as follows:The content of chemistry appeared in the first rank with a percentage (49.15) of (115) iterations, and the physics content came in the second place with a percentage of (25.64) and (60) iterations, and the content of biology came in the third place with (59) iterations with a percentage of (25.21), as for the content of earth sciences, the percentage was (0) zero. As for the results of the areas of the cognitive dimension in the science book for the first intermediate grade, the field of understanding outperformed in the first rank with a percentage of (42.89), with a rate of (293) recurrences, the field of knowledge ranked second with a rate of (41.72) and (285) recurrences, and the field of application ranked third with a rate of (15.39) and (105) recurrence, in light of these research results, the researcher reached a number of conclusions, recommendations and suggestions.